(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2021)
Wave particle duality is a cornerstone of quantum chemistry and quantum mechanics (QM). But there are experiments it cannot explain, such as a neutron interferometer experiment. If QM uses Ψ as its wavefunction, several experiments suggest that nature uses -Ψ instead. The difference between -Ψ and +Ψ is that they describe entirely different pictures of how nature is organized. For example, with -Ψ quantum particles follow waves backwards, which is incompatible with wave-particle-duality, obviously. We call the -Ψ proposal the Theory of Elementary Waves (TEW). It unlocks opportunities for young scientists with no budget to conduct the basic research for a new, unexplored science. This is a dream come true for young scientists: the discovery of uncharted territory. We show how TEW explains the double slit, Pfleegor Mandel and Davisson Germer experiments, Feynman diagrams and the Bell test experiments. We provide innovative research designs for which -Ψ and +Ψ would predict divergent outcomes. What makes QM so accurate is its probability predictions. But Born’s law would yield the same probabilities if it were changed from P = |+Ψ |2 to P = |-Ψ |2. This article is accompanied by a lively YouTube video, “6 reasons to discard wave particle duality.”